SAE Technical Paper Series 2004
DOI: 10.4271/2004-01-2903
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ambient Temperature on Cold Start Urban Traffic Emissions for a Real World SI Car

Abstract: The influence of ambient temperature on exhaust emissions for an instrumented Euro 1 SI car was determined. A real world test cycle was used, based on an urban drive cycle that was similar to the ECE urban drive cycle. It was based on four laps of a street circuit and an emissions sample bag was taken for each lap. The bag for the first lap was for the cold start emissions. An in-vehicle direct exhaust dual bag sampling technique was used to simultaneously collect exhaust samples upstream and downstream of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…However, the excess emissions for the second phase (the EUDC) were around 13%, indicating that the ambient temperature still had an effect on fuel consumption (and therefore on CO 2 emissions), despite the engine being more or less fully warmed up by the time the second phase started. HC and PM showed very large increases during both phases; CO and NO x only showed a large increase during the fi rst phase (the UDC); deterioration in emissions of CO 2 and PN and in the fuel consumption were less dramatic. The elevated emissions of HC and CO during the fi rst phase strongly suggest combustion diffi culties and rich operation.…”
Section: Hc and Co Emissions Results From Mpi And Disi Vehicles Obtainementioning
confidence: 97%
See 1 more Smart Citation
“…However, the excess emissions for the second phase (the EUDC) were around 13%, indicating that the ambient temperature still had an effect on fuel consumption (and therefore on CO 2 emissions), despite the engine being more or less fully warmed up by the time the second phase started. HC and PM showed very large increases during both phases; CO and NO x only showed a large increase during the fi rst phase (the UDC); deterioration in emissions of CO 2 and PN and in the fuel consumption were less dramatic. The elevated emissions of HC and CO during the fi rst phase strongly suggest combustion diffi culties and rich operation.…”
Section: Hc and Co Emissions Results From Mpi And Disi Vehicles Obtainementioning
confidence: 97%
“…Overall, in the last 13 years, maximum permissible emissions from SI engines have decreased by around 40%; emissions limits for CI engines are now roughly 80% lower than they were. (Note that these reductions are for regulated emissions and do not include CO 2 , which has its own legislation).…”
Section: Archives Of Environmental Protection Vol 40 No 3 Pp 86 -1mentioning
confidence: 99%
“…For cold start emission control it is the light off of the first brick that is important, but having both bricks active is important in terms of achieving the best catalyst conversion efficiency. (30), in which authors reported that the HC and CO emissions were strongly depending on thermal warm up processes of engine and exhaust system and affected by ambient temperatures. Figures 27 and 28 show the HC and CO emissions as a function of warm up process and comparisons between winter and summer.…”
Section: Catalyst Inlet Gas Temperatures and Energy Gain -mentioning
confidence: 99%
“…This demonstrated that hydrocarbon emissions were not as sensitive as CO emissions to engine temperatures. Li et al [6,[29][30][31][32] investigated cold start emissions from SI passenger cars and a light duty diesel van and reported a greater increase in CO emissions than hydrocarbon emissions when the temperature of the engine in a vehicle was lower.…”
Section: Hydrocarbon Emissionsmentioning
confidence: 99%